Molecular Portrait of GISTs Associated With Clinicopathological Features: A Retrospective Study With Molecular Analysis by a Custom 9-Gene Targeted Next-Generation Sequencing Panel - Qian, Haoran; Yan, Na; Hu, Xiaotong; Jiang, Junchang; Cao, Zhengzheng; Shen, Dan (Frontiers in Genetics, 2022)
Objectives: The study aims to investigate genetic characterization of molecular targets and clinicopathological features with gastrointestinal stromal tumors based on targeted next-generation sequencing. Materials and methods: We collected 106 Patients with GIST from Sir Run Run Shaw Hospital between July 2019 and March 2021. FFPE samples and paired blood samples were obtained from these patients who underwent excision of tumor. A customized targeted-NGS panel of 9 GIST-associated genes was designed to detect variants in the coding regions and the splicing sites of these genes. Results: In total, 106 patients with a GIST were included in the study which presented with various molecular driver alterations in this study. KIT mutations occurred most often in GISTs (94/106, 95.92%), followed by point mutation in PDGFRA. KIT or PDGFRA mutations were detected to be mutually exclusive in GIST. 8 patients with wide-type KIT/PDGFRA were characterized as WT-GISTs according to clinical diagnosis which included 6 quadruple-WT GISTs, 1 BRAF-mutant and 1 NF1-mutant GIST. In KIT exon 11, the most common mutation type was Condon Mutation (in-frame deletion or indels), whereas the missense mutation was the dominant type in KIT exon13 and KIT exon 17. All variations in KIT exon 11 observed in this study were concentrated at certain position of codon 550 to codon 576. Mutation in KIT exon9 mostly located at codon 502-503. Two germline pathogenic mutations were detected, NF1-R681* and KRAS-T58I. NF1-L591P was a germline mutation to be identified for the first time and not recorded in the database. The frequency of driving mutations differed between primary anatomical site in GIST (P = 0.0206). KIT exon11 mutants had lower proliferation index of Ki67(68.66%,≤5%), while 50.00% of KIT exon9 mutants had Ki67 status greater than 10%. Conclusion: The occurrence and development of GIST is driven by different molecular variations. Resistance to TKIs arise mainly with resistance mutations in KIT or PDGFRA when they are the primary drivers. Targeted NGS can simultaneously and efficiently detect 9 GIST related gene mutations, and provide reference for clinicians' individualized diagnosis and treatment. Our results have important implications for clinical management.